Modification of biochemical and haematological parameters during 90-days subchronic toxicity assessment of Carissa edulis in Wistar rats - Osseni, Razack; ADANLE, Etienne; ADJAGBA, Marius; AWEDE, BONAVENTURE L. SÉVERIN; HOUNTOHOTEGBE, Tatiana; BIGOT, KOFFI ANDRÉ; DARBOUX, RAPHAËL BARTHÉLÉMY; LALEYE, OLABISSI ANATOLE A. (My University, 2017)
A 90-days subchronic toxicity assay was evaluated on the aqueous extract of Carissa edulis leaves. Wistar rats were fed daily with oral doses of 125, 31.25 and 7.87 mg/kg of C. edulis leaves extracts. Toxic effects were assessed using physiological observation, body weight, relative organ weights, feed consumption, biochemical, haematological and histopathological parameters. Many changes of biological values were observed among treated rats versus controls. Although, alterations in biochemical parameters including aspartate amino transferase were observed, in the middle of treatment (day 45), the values were physiologically normalized at the end of the study. Changes were observed also among renal function parameters including increased levels of creatinine, urea and ions disorders. These results were related by the histopathological examinations. The haematological analysis showed an increase in erythrocytes count, haemoglobin, haematocrit (polyerythrocythemia) associated with an increase of MGV level (macrocytosis). These observations suggest that the longterm uses of Carissa edulis could alter some functions of the organism, especially the hepatic, renal and haematopoietic functions. Further specific toxicity studies must be investigated on the plant.
Keywords: Carissa edulis; polyerthrocythemia; subchronic toxicity; Wistar rats